Leadership in Indonesian Islamic Schools: How Leader Spiritual and Motivational Styles Affect Organizational Citizenship Behavior and Employees' Religiosity - Nadia Nur ifani; Asti Putri Kartiwi (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
The history of Islamic education in Indonesia has experienced fluctuations over time. Until the late 1970s, the education system in Indonesia retained a strong dichotomous pattern. With the onset of reforms in the 1980s, the Muslim community began to reform its education system, which impacted the development of Islamic education in Indonesia. This is evident from the significant growth of integrated Islamic educational institutions across various levels in major cities in Indonesia. Of course, enhancing the quality of the educational process must accompany this increase. Teachers and staff play a crucial role in maintaining the quality of the educational process in schools. This research examines whether a school principal's spiritual leadership style and motivational style influence the organizational citizenship behavior among teachers and staff in Islamic schools in Bengkulu City. A proportional random sampling technique was used to select a sample of 100 respondents from these institutions, consisting of teachers and staff. Participants were asked to complete a Likert scale survey administered through Google Forms. Subsequently, the obtained data underwent multiple linear regression analysis. This research identifies the correlation between Organizational Citizenship Behavior (OCB), adherence to spiritual principles, and workplace motivation. This research aims to enhance the understanding of education stakeholders, particularly in Islamic education, by highlighting the potential positive relationship between religious devotion and increased motivation among instructors and personnel in these institutions.